Nash, The Crucial Era - The Great Drepression and World War II. 1929-1945 - Fuller, Paul (Teaching History: A Journal of Methods, 1994)
In the second edition of this useful and highly interpretive survey, Gerald D. Nash, professor of history at the University of New Mexico, describes the years from 1929 to 1945 as "some of the most fateful and decisive in the history of the United States." While combating a Great Depression in the thirties and waging a World War in the forties, Nash contends that the United States underwent an "organizational revolution" that restructured its economy and society, setting itself on a course, radically different from the past, which has persisted to the present day.